CONTRASTIVE ANALYSIS OF THE MEANING OF JAPANESE AND INDONESIAN PROVERBS FORMED FROM WORDS犬 (DOG) AND 猫 (CAT) - Ranti Maulidyanti; Novia Hayati; Herniwati Herniwati (JOMANTARA, 2023)
This study aims to compare the differences and similarities in the meaning of proverbs in Japanese and Indonesian using the words dog and cat. This research was designed with a qualitative descriptive research design. The method used to describe research objects in words. The data for this research are 143 proverbs in Indonesian and Japanese that use the words 犬 (dog) and 猫 (cat) with the analytical technique used is contrastive analysis. Based on the results of data analysis, it was found that there are differences and similarities between Japanese proverbs and Indonesian proverbs that use the words 犬 (dog) and 猫 (cat). Meanwhile, based on these findings, the conclusions of this research are as follows: Japanese proverbs are special sentences that form is fixed, and their constituent elements cannot be changed. In other words, Japanese proverbs do not follow grammatical rules like in ordinary sentences. Based on the analysis of the structure of Japanese proverbs containing the words dog and cat, the proverbs use the comparison of words in a sentence. Japanese proverbs use numbers, expository descriptions, and impressionistic descriptions to correlate two or more things. Japanese proverbs have two meanings; lexical meaning and idiomatic meaning. Likewise, the meaning of the Indonesian proverb, which contains elements of dogs and cats, representing that dogs are a nuisance and a hindrance but are viewed positively as animals loyal to their masters. In contrast, cats are described as cute animals, but only close in the domestic area. Both of them interpret the same dog as a fierce animal, scary but loyal, to their masters. Both languages ​​equate to betrayal committed by those closest to us as a form of dog disloyalty to their masters because, naturally, the closest people to us are like dogs, loyal to their masters. As for the suggestions/recommendations in this study, further research should be carried out regarding Japanese proverbs containing dogs and cats with proverbs. Regional languages ​​in Indonesia are rich in forms of proverbs containing the words dogs and cats, but this must be done using different analytical techniques. For example, by pragmatic analysis or functional linguistic systems initiated by Haliday in 1972.